Combined composite material cylindrical shell and preparation method thereof

By using a combination design of glass fiber and modified epoxy resin in fiber composite materials, and combining the winding technology of carbon fiber composite materials, the shortcomings of existing materials in terms of mechanical properties, corrosion resistance and aging resistance are solved, and higher mechanical properties and longer service life are achieved.

CN119684749AInactive Publication Date: 2025-03-25XINXIANG UNIV

Patent Information

Application Number
CN202510202554.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fiber composite materials have shortcomings in mechanical properties, corrosion resistance, aging resistance and axial load bearing capacity, which is difficult to meet the modern industry's demand for high-performance structural materials.

Method used

The design of a combined composite cylindrical shell is adopted, and the toughness and mechanical properties of the material are improved by proportioning glass fibers and modified epoxy resins in a specific proportion, and by the preparation method of modified epoxy resins, including surface modification and ultrasonic dispersion of nanofillers. At the same time, carbon fiber composite materials are used for external winding to enhance the axial load-bearing capacity.

Benefits of technology

It significantly improves the tensile, compressive and flexural strength of composite materials, extends the service life of the material in harsh environments, and improves the efficiency and cost control of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of fiber composite materials, in particular to a combined composite material cylindrical shell and a preparation method thereof. The cylindrical shell comprises a plurality of composite material splicing blocks, and each composite material splicing block is prepared from the following raw materials in parts by weight: 40 to 60 parts of glass fiber and 30 to 50 parts of modified epoxy resin; the modified epoxy resin is prepared from the following raw materials in parts by weight: 100 parts of epoxy resin, 15 to 20 parts of carboxy nitrile rubber, 5 to 10 parts of bisphenol A glycidyl ether, 5 to 10 parts of polyether amine, 0.3 to 0.5 part of antioxidant, 5 to 8 parts of preservative, 60 to 80 parts of curing agent, 0.5 to 1.5 parts of accelerant and 5 to 8 parts of nano filler. The mechanical property, the corrosion resistance, the aging resistance and the axial bearing capacity of the cylindrical shell are remarkably improved. The preparation method disclosed by the invention has the characteristics of high efficiency and continuity, and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber composite materials, and in particular to a combined composite cylindrical shell and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, the demand for high-performance structural materials is growing. In many fields, such as civil engineering, aerospace, offshore wind power, etc., higher requirements are put forward for the mechanical properties, corrosion resistance, aging resistance and axial load-bearing capacity of materials. Although traditional metal materials have certain strength and toughness, their corrosion resistance and aging resistance are poor under complex working conditions, such as marine environment or industrial corrosion environment, and their service life is limited. In addition, their weight is large, which affects the lightweight design of the structure. Although traditional fiber composite materials have advantages in some properties, there are still some technical bottlenecks in large-scale production, such as low production efficiency and high cost.

[0003] In the field of fiber composite materials, there are still some deficiencies in the performance and preparation process of existing fiber composite materials. For example, the mechanical properties of fiber composite materials need to be further improved to meet more stringent use requirements; in terms of corrosion resistance and aging resistance, the performance of existing materials still needs to be optimized to extend their service life in harsh environments; in addition, the existing preparation methods also have certain limitations in efficiency and cost control during large-scale production.

[0004] Chinese patent document CN201610235881.4 discloses a carbon fiber reinforced epoxy resin composite material, which comprises, by weight, 45 to 60 parts of epoxy resin, 10 to 15 parts of toughening agent, 4 to 5 parts of lubricant, 15 to 20 parts of curing agent, 1 to 2 parts of accelerator, 5 to 10 parts of thickener, 1 to 3 parts of release agent, 5 to 10 parts of compatibilizer, 10 to 15 parts of nano-barium sulfate, 8 to 12 parts of UHMWPE, and 10 to 16 parts of carbon fiber. Although the prepared carbon fiber reinforced epoxy resin composite material has good scratch resistance, the mechanical properties of the composite material still need to be improved. Chinese patent document CN202211085022.3 discloses a modified carbon fiber, a preparation method and application thereof, and a modified carbon fiber epoxy resin composite material. By introducing a graphene oxide film layer on the surface of the carbon fiber with a π-π force, the surface of the carbon fiber is made chemically active and rougher, thereby improving the wettability with the resin matrix, forming a strong interaction, and enhancing the interface performance of the composite material. However, the aging resistance of the material is insufficient. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a combined composite cylindrical shell, which significantly improves its mechanical properties, corrosion resistance, aging resistance and axial load-bearing capacity, so that it has broad application prospects and economic benefits in the fields of civil engineering, aerospace, marine wind power, etc. The preparation method of the present invention is characterized by high efficiency and continuity, and is suitable for large-scale production.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A combined composite cylindrical shell, the cylindrical shell comprising a plurality of composite splicing blocks, the composite splicing blocks comprising the following raw materials by weight: 40-60 parts of glass fiber, 30-50 parts of modified epoxy resin; the modified epoxy resin comprising the following raw materials by weight: 100 parts of epoxy resin, 15-20 parts of carboxyl nitrile rubber, 5-10 parts of bisphenol A glycidyl ether, 5-10 parts of polyether amine, 0.3-0.5 parts of antioxidant, 5-8 parts of preservative, 60-80 parts of curing agent, 0.5-1.5 parts of accelerator, 5-8 parts of nano filler; The preparation method of the modified epoxy resin is as follows: Step 1, mixing the nanofiller and the silane coupling agent in a mass ratio of 100:0.8-1.3, then adding them to anhydrous ethanol, performing ultrasonic dispersion at a frequency of 40-60kHz for 20-40 minutes, and then vacuum drying and removing the solvent to obtain a surface-modified nanofiller; Step 2, adding carboxylated nitrile rubber, bisphenol A glycidyl ether, polyetheramine and the surface-modified nanofiller of step 1 into the epoxy resin, and stirring to make them uniformly dispersed; Step 3, adding antioxidants and preservatives to the mixed material obtained in step 2 in sequence, stirring and mixing; Step 4, adding the curing agent and the accelerator to the mixed material obtained in step 3, stirring at a speed of 250-350 rpm for 20-40 minutes, mixing, and then degassing under vacuum conditions for 20-40 minutes until there are no bubbles on the resin surface; Step 5, pre-curing the material after degassing in step 4 at a temperature of 100-120° C. for 1.5-2.5 hours.

[0007] Glass fiber is used as a reinforcement to provide high strength and high modulus, and modified epoxy resin is used as a matrix material. By introducing a variety of modifiers, the toughness and mechanical properties of the composite material are significantly improved. The reasonable ratio of glass fiber and modified epoxy resin ensures that the composite material has excellent toughness and impact resistance while maintaining high strength, and the overall performance is improved.

[0008] In modified epoxy resin, the addition of carboxylated nitrile rubber can effectively improve the toughness of epoxy resin, prevent crack generation and expansion, and improve the fracture toughness of the material. Its elastomeric properties can absorb and disperse stress and reduce stress concentration. The molecular structure of bisphenol A glycidyl ether contains flexible ether bonds, which can reduce the cross-linking density of the resin and improve the flexibility of the molecular chain. When the cylindrical shell is impacted by external force, these flexible structures can effectively disperse stress, prevent crack expansion, prevent brittle fracture, enhance the impact resistance of the material, and maintain structural integrity under complex stress environments. Polyetheramine is introduced into the resin matrix as a flexible chain segment to improve the flexibility and fatigue resistance of epoxy resin, thereby enabling the composite material to maintain good mechanical properties under long-term cyclic loads. Bisphenol A glycidyl ether works synergistically with carboxylated nitrile rubber and polyetheramine to jointly improve the toughness of epoxy resin. At the same time, bisphenol A glycidyl ether can also reduce the viscosity of the epoxy resin system and improve fluidity. During the dipping process, the modified epoxy resin helps to better impregnate the glass fiber, ensuring uniform impregnation of the glass fiber, avoiding uneven impregnation and defects caused by high resin viscosity, improving the quality of composite material splicing blocks, enhancing the interface bonding strength between glass fiber and resin, and improving the overall mechanical properties of the cylindrical shell.

[0009] The epoxy groups in the bisphenol A glycidyl ether molecule can also react with the curing agent, participate in the construction of the epoxy resin cross-linking network, adjust the cross-linking structure, and make the cured resin have better performance. Moderate participation in cross-linking can optimize the cross-linking density, balance the hardness, flexibility and strength of the material, and meet the performance requirements of the cylindrical shell in different application scenarios. The addition of nanofillers can fill the microscopic pores of the resin matrix and improve the density and mechanical properties of the material. At the same time, the high specific surface area of ​​the nanofillers can enhance the interfacial bonding with the resin matrix and further improve the strength and modulus of the modified epoxy resin.

[0010] In the preparation process of modified epoxy resin, the nanofiller is surface modified by silane coupling agent to improve its compatibility with the resin matrix, avoid agglomeration, and improve dispersion uniformity. Ultrasonic dispersion and vacuum drying processes ensure uniform dispersion and surface modification of the nanofiller. The vacuum degassing process can remove bubbles in the resin and improve the density, mechanical properties and strength of the material.

[0011] Preferably, the nanofiller is nano-silicon dioxide with a particle size of 20-50 nm.

[0012] Preferably, the curing agent is methyltetrahydrophthalic anhydride.

[0013] Preferably, the accelerator is 2-ethyl-4-methylimidazole.

[0014] Preferably, the antioxidant is a hindered phenol antioxidant.

[0015] Preferably, the preservative is a flaky zinc-aluminum complex.

[0016] Preferably, the preparation method of the flaky zinc-aluminum composite is: Step A, dissolving zinc nitrate hexahydrate and aluminum nitrate nonahydrate in deionized water, wherein the molar ratio of zinc to aluminum is 2-3:1; Step B, stirring and reacting for 2-4 hours under alkaline conditions of pH = 9-10 to generate a precursor precipitate; Step C, hydrothermally aging at 60-80° C. for 12-24 hours, followed by washing and drying to obtain a flaky zinc-aluminum composite.

[0017] The flaky zinc-aluminum composite has a unique layered structure. The activity of zinc makes it preferentially oxidize when it contacts the corrosive medium, generating an insoluble composite to seal the corrosive medium, forming a physical barrier to prevent further penetration of the corrosive medium. At the same time, the layered structure can effectively block the diffusion path of corrosive substances and delay the erosion of the base material by corrosive substances. Nano zinc oxide has a large specific surface area, high activity, and good adsorption properties. It can be adsorbed on the surface of the material to form a dense protective film, further blocking the invasion of corrosive media. The two work together from different mechanisms to significantly enhance the anti-corrosion effect. In addition to the anti-corrosion effect, nano zinc oxide can also improve the hardness, wear resistance and other properties of the material. The stacked structure of the flaky zinc-aluminum composite can form a tight barrier structure on the resin surface, and the nano zinc oxide fills the gaps in the flaky zinc-aluminum composite, further improving the density, hardness, wear resistance, etc., optimizing the overall physical properties of the material, so that the composite material has better mechanical properties while being corrosion-resistant, and is suitable for a variety of complex working conditions.

[0018] The method for preparing the above-mentioned combined composite cylindrical shell, the method for preparing the composite splicing block comprises the following steps: Step S1, pretreatment of glass fiber: soaking the glass fiber in a 3%-5% silane coupling agent aqueous solution for 20-30 minutes, and then drying at 100-120° C. for 2-3 hours; Step S2, pouring the pre-cured modified epoxy resin into a dipping tank, maintaining the temperature at 80-90° C., passing the pre-treated glass fiber through the dipping tank, and controlling the dipping speed at 0.3-0.5 m / min to make the glass fiber evenly impregnated with the modified epoxy resin; Step S3, preheating the mold to 120-150°C, extruding the impregnated glass fiber into the mold through an extruder at a speed of 0.5-1m / min to form a block, and then curing it at a temperature of 120-150°C for 2-4 hours to obtain a composite material splicing block.

[0019] Preferably, a plurality of composite material splicing blocks are spliced ​​together to form a cylindrical shell structure, and then a carbon fiber composite material is continuously wound around the outside of the cylindrical shell to obtain a composite material cylindrical shell.

[0020] In the preparation of composite material splicing blocks, the glass fiber is first pretreated with a silane coupling agent to improve its interfacial bonding with the resin matrix and improve the mechanical properties of the composite material. The impregnation temperature and impregnation speed are controlled to ensure that the glass fiber is evenly impregnated with the modified epoxy resin to avoid excessive or insufficient resin affecting the material properties. After the composite material splicing blocks are spliced ​​into a cylindrical shell structure, carbon fiber composite materials are used for continuous circumferential winding on the outside of the cylindrical shell. The high strength and high modulus of carbon fiber can further improve the axial bearing capacity of the cylindrical shell. At the same time, the tension applied during the winding process can form prestress inside the cylindrical shell, improving its compressive and bending resistance.

[0021] The present invention has the following beneficial effects: The combined composite cylindrical shell of the present invention has significantly improved tensile strength, compressive strength and flexural strength through the optimization of formula and process. The fracture toughness and impact resistance are improved, so that it is not easy to have brittle fracture when subjected to external force.

[0022] Furthermore, the optimization of preservatives and the addition of nanofillers significantly improve the corrosion resistance of the composite material, especially in harsh environments (such as marine environments or industrial corrosion environments) with a longer service life. Antioxidants effectively inhibit the oxidative degradation of the resin matrix and extend the service life of the cylindrical shell.

[0023] The preparation method of the present invention adopts an extrusion molding process, which is efficient and continuous and suitable for large-scale production. The combined composite cylindrical shell obtained by the preparation method of the present invention significantly improves its mechanical properties, corrosion resistance, aging resistance and axial bearing capacity, so that it has broad application prospects and economic benefits in the fields of civil engineering, aerospace, marine wind power, etc. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0025] The raw materials used in the following examples are all common commercial products. Glass fiber, elongation at break 2.45%; epoxy resin, E-44 epoxy resin, Shandong Zhengyu Chemical Technology Co., Ltd.; carboxylated nitrile rubber, effective ingredient content 99%, Hubei Xinyuhong Biomedical Technology Co., Ltd.; bisphenol A glycidyl ether effective ingredient content 99%, brand Yamade; polyetheramine, model, D-2000, Jiangsu Minglin Chemical Technology Co., Ltd.; methyltetrahydrophthalic anhydride, content 99%, Jinan Mingxin Chemical Co., Ltd.; 2-ethyl-4-methylimidazole, content 99%, Jiangsu Pules Biotechnology Co., Ltd.; hindered phenol antioxidant, model Irganox 1010, purchased from Jiangyin Wanqian Chemical Co., Ltd.; silane coupling agent KH550. Example 1

[0026] A composite cylindrical shell, the cylindrical shell comprises a plurality of composite splicing blocks, the composite splicing blocks comprise the following raw materials by weight: 50 parts of glass fiber, 40 parts of modified epoxy resin; the modified epoxy resin comprises the following raw materials by weight: 100 parts of epoxy resin, 18 parts of carboxylated nitrile rubber, 7 parts of bisphenol A glycidyl ether, 7 parts of polyetheramine, 0.4 parts of antioxidant, 7 parts of preservative, 75 parts of curing agent, 1 part of accelerator, 6 parts of nano filler; the nano filler is nano silicon dioxide with a particle size of 20-50nm. The curing agent is methyl tetrahydrophthalic anhydride. The accelerator is 2-ethyl-4-methylimidazole. The antioxidant is a hindered phenol antioxidant. The preservative is a flaky zinc-aluminum composite.

[0027] The preparation method of the modified epoxy resin is as follows: Step 1, mixing the nanofiller and the silane coupling agent in a mass ratio of 100:1, then adding them to anhydrous ethanol, ultrasonically dispersing them at a frequency of 50 kHz for 30 minutes, the weight volume ratio of the nanofiller to the anhydrous ethanol being 1:3.2, and then vacuum drying them at 60° C. for 2 hours to remove the solvent, thereby obtaining a surface-modified nanofiller; Step 2, adding carboxylated nitrile rubber, bisphenol A glycidyl ether, polyetheramine and the surface-modified nanofiller of step 1 to the epoxy resin, stirring at a speed of 500 rpm for 90 minutes to make it uniformly dispersed; Step 3, adding antioxidants and preservatives to the mixture obtained in step 2 in sequence, stirring for 1 hour, and then further dispersing using a three-roll mill at a speed of 200 rpm for 30 minutes to mix well; Step 4, adding the curing agent and the accelerator to the mixed material obtained in step 3, stirring at a speed of 300 rpm for 30 minutes, mixing, and then degassing at a vacuum degree of -0.1 MPa for 30 minutes until there are no bubbles on the surface; Step 5, pre-curing the material after the degassing treatment in step 4 at a temperature of 110° C. for 2 hours.

[0028] The preparation method of the flaky zinc-aluminum composite is as follows: Step A, dissolving zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) in deionized water, the weight volume ratio of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) to water is 100 g:1 L, and the molar ratio of zinc to aluminum is 2.5:1; Step B, prepare 0.5 mol / L NaOH and 0.1 mol / L Na2CO3 solution, mix them in a volume ratio of 1:1, and add them dropwise to the solution obtained in step A until the pH value is 9-10. After the addition is completed, continue to stir and react for 3 hours until a milky white precipitate is generated; Step C, adding the material mixture after the reaction in step B into a high-pressure reactor, hydrothermally aging for 20 hours at a stirring speed of 150 rpm and 70° C., then centrifuging for 10 minutes at 9000 rpm, collecting the precipitate, repeating the centrifugation 3 times, and then washing the obtained precipitate once with deionized water, and then washing twice with anhydrous ethanol (to reduce particle agglomeration during drying), and finally vacuum drying at a temperature of 60° C., a vacuum degree of ≤-0.09 MPa, and a drying time of 24 hours to obtain a flaky zinc-aluminum composite.

[0029] The method for preparing the above-mentioned combined composite cylindrical shell comprises the following steps: Step S1, pretreatment of glass fiber: soaking the glass fiber in a 4% silane coupling agent aqueous solution for 25 minutes, and then drying at 110° C. for 2.5 hours; Step S2, pouring the pre-cured modified epoxy resin into a dipping tank, maintaining the temperature at 85° C., passing the pre-treated glass fiber through the dipping tank, and controlling the dipping speed at 0.4 m / min to make the glass fiber evenly impregnated with the modified epoxy resin; Step S3, preheating the mold to 140° C., extruding the impregnated glass fiber into the mold at a speed of 0.7 m / min through an extruder to form a block, and then curing it at a temperature of 140° C. for 3 hours to obtain a composite material splicing block; Step S4, splicing a plurality of composite material splicing blocks to form a cylindrical shell structure, and then using carbon fiber composite materials to continuously circumferentially wind 4 layers on the outside of the cylindrical shell with a winding tension of 75N / bundle, to obtain a composite material cylindrical shell. Example 2

[0030] A composite cylindrical shell, the cylindrical shell comprises a plurality of composite splicing blocks, the composite splicing blocks comprise the following raw materials by weight: 55 parts of glass fiber, 35 parts of modified epoxy resin; the modified epoxy resin comprises the following raw materials by weight: 100 parts of epoxy resin, 15 parts of carboxylated nitrile rubber, 6 parts of bisphenol A glycidyl ether, 10 parts of polyetheramine, 0.3 parts of antioxidant, 5 parts of preservative, 70 parts of curing agent, 1.2 parts of accelerator, 7 parts of nano filler; the nano filler is nano silicon dioxide with a particle size of 20-50nm. The curing agent is methyl tetrahydrophthalic anhydride. The accelerator is 2-ethyl-4-methylimidazole. The antioxidant is a hindered phenol antioxidant. The preservative is a flaky zinc-aluminum composite.

[0031] The preparation method of the modified epoxy resin is as follows: Step 1, mixing the nanofiller and the silane coupling agent in a mass ratio of 100:1, then adding them to anhydrous ethanol, ultrasonically dispersing them at a frequency of 40 kHz for 40 minutes, the weight volume ratio of the nanofiller to the anhydrous ethanol being 1:3, and then vacuum drying them at 65° C. for 1.5 hours to remove the solvent, thereby obtaining a surface-modified nanofiller; Step 2, adding carboxylated nitrile rubber, bisphenol A glycidyl ether, polyetheramine and the surface-modified nanofiller of step 1 to the epoxy resin, stirring at a speed of 500 rpm for 90 minutes to make it uniformly dispersed; Step 3, adding antioxidants and preservatives to the mixture obtained in step 2 in sequence, stirring for 1 hour, and then further dispersing using a three-roll mill at a speed of 200 rpm for 30 minutes to mix well; Step 4, adding the curing agent and the accelerator to the mixed material obtained in step 3, stirring at a speed of 250 rpm for 40 minutes, mixing, and then degassing for 40 minutes under a vacuum degree of -0.1 MPa until there are no bubbles on the surface; Step 5, pre-curing the material after degassing in step 4 at a temperature of 100° C. for 2.5 hours.

[0032] The preparation method of the flaky zinc-aluminum composite is as follows: Step A, dissolving zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) in deionized water, the weight volume ratio of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) to water is 105 g:1 L, and the molar ratio of zinc to aluminum is 3:1; Step B, prepare 0.5 mol / L NaOH and 0.1 mol / L Na2CO3 solution, mix them in a volume ratio of 1:1, and add them dropwise to the solution obtained in step A until the pH value is 9-10. After the addition is completed, continue to stir and react for 2 hours until a milky white precipitate is generated; Step C, adding the material mixture after the reaction in step B into a high-pressure reactor, hydrothermally aging for 18 hours at a stirring speed of 200 rpm and 60° C., then centrifuging at 8000 rpm for 12 minutes, collecting the precipitate, repeating the centrifugation 3 times, and then washing the obtained precipitate once with deionized water, and then washing twice with anhydrous ethanol (to reduce particle agglomeration during drying), and finally vacuum drying at a temperature of 60° C., a vacuum degree of ≤-0.09 MPa, and a drying time of 24 hours to obtain a flaky zinc-aluminum composite.

[0033] The method for preparing the above-mentioned combined composite cylindrical shell comprises the following steps: Step S1, pretreatment of glass fiber: soaking the glass fiber in a 5% silane coupling agent aqueous solution for 30 minutes, and then drying at 120° C. for 2 hours; Step S2, pouring the pre-cured modified epoxy resin into a dipping tank, maintaining the temperature at 90° C., passing the pre-treated glass fiber through the dipping tank, and controlling the dipping speed at 0.3 m / min to make the glass fiber evenly impregnated with the modified epoxy resin; Step S3, preheating the mold to 150° C., extruding the impregnated glass fiber into the mold at a speed of 0.8 m / min through an extruder to form a block, and then curing it at a temperature of 120° C. for 4 hours to obtain a composite material splicing block; Step S4, splicing a plurality of composite material splicing blocks to form a cylindrical shell structure, and then using carbon fiber composite materials to continuously circumferentially wind 5 layers on the outside of the cylindrical shell with a winding tension of 50N / bundle, to obtain a composite material cylindrical shell. Example 3

[0034] A composite cylindrical shell, the cylindrical shell comprises a plurality of composite splicing blocks, the composite splicing blocks comprise the following raw materials by weight: 60 parts of glass fiber, 30 parts of modified epoxy resin; the modified epoxy resin comprises the following raw materials by weight: 100 parts of epoxy resin, 20 parts of carboxylated nitrile rubber, 10 parts of bisphenol A glycidyl ether, 5 parts of polyetheramine, 0.5 parts of antioxidant, 8 parts of preservative, 60 parts of curing agent, 1.5 parts of accelerator, 8 parts of nano filler; the nano filler is nano silicon dioxide with a particle size of 20-50nm. The curing agent is methyl tetrahydrophthalic anhydride. The accelerator is 2-ethyl-4-methylimidazole. The antioxidant is a hindered phenol antioxidant. The preservative is a flaky zinc-aluminum composite.

[0035] The preparation method of the modified epoxy resin is as follows: Step 1, mixing the nanofiller and the silane coupling agent in a mass ratio of 100:0.8, then adding them to anhydrous ethanol, and ultrasonically dispersing them at a frequency of 60 kHz for 20 minutes, the weight volume ratio of the nanofiller to the anhydrous ethanol being 1:3.5, and then vacuum drying at 55° C. for 2.5 hours to remove the solvent, thereby obtaining a surface-modified nanofiller; Step 2, adding carboxylated nitrile rubber, bisphenol A glycidyl ether, polyetheramine and the surface-modified nanofiller of step 1 to the epoxy resin, stirring at a speed of 500 rpm for 90 minutes to make it uniformly dispersed; Step 3, adding antioxidants and preservatives to the mixture obtained in step 2 in sequence, stirring for 1 hour, and then further dispersing using a three-roll mill at a speed of 200 rpm for 30 minutes to mix well; Step 4, adding the curing agent and the accelerator to the mixed material obtained in step 3, stirring at a speed of 350 rpm for 20 minutes, mixing, and then degassing for 20 minutes under a vacuum degree of -0.1 MPa until there are no bubbles on the surface; Step 5, pre-curing the material after the degassing treatment in step 4 at a temperature of 120° C. for 1.5 hours.

[0036] The preparation method of the flaky zinc-aluminum composite is as follows: Step A, dissolving zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) in deionized water, the weight volume ratio of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) to water is 115 g:1 L, and the molar ratio of zinc to aluminum is 2:1; Step B, prepare 0.5 mol / L NaOH and 0.1 mol / L Na2CO3 solution, mix them in a volume ratio of 1:1, and add them dropwise to the solution obtained in step A until the pH value is 9-10. After the addition is completed, continue to stir and react for 4 hours until a milky white precipitate is generated; Step C, adding the material mixture after the reaction in step B into a high-pressure reactor, hydrothermally aging for 12 hours at a stirring speed of 100 rpm and 80° C., then centrifuging at 10,000 rpm for 8 minutes, collecting the precipitate, repeating the centrifugation 3 times, and then washing the obtained precipitate once with deionized water, and then washing twice with anhydrous ethanol (to reduce particle agglomeration during drying), and finally vacuum drying at a temperature of 60° C., a vacuum degree of ≤-0.09 MPa, and a drying time of 24 hours to obtain a flaky zinc-aluminum composite.

[0037] The method for preparing the above-mentioned combined composite cylindrical shell comprises the following steps: Step S1, pretreatment of glass fiber: soaking the glass fiber in a 3% silane coupling agent aqueous solution for 20 minutes, and then drying at 100° C. for 3 hours; Step S2, pouring the pre-cured modified epoxy resin into a dipping tank, maintaining the temperature at 80° C., passing the pre-treated glass fiber through the dipping tank, and controlling the dipping speed at 0.5 m / min to make the glass fiber evenly impregnated with the modified epoxy resin; Step S3, preheating the mold to 120° C., extruding the impregnated glass fiber into the mold at a speed of 0.5 m / min through an extruder to form a block, and then curing it at a temperature of 150° C. for 2 hours to obtain a composite material splicing block; Step S4, splicing a plurality of composite material splicing blocks to form a cylindrical shell structure, and then using carbon fiber composite materials to continuously circumferentially wind 5 layers on the outside of the cylindrical shell with a winding tension of 70N / bundle, to obtain a composite material cylindrical shell. Example 4

[0038] A composite cylindrical shell, the cylindrical shell comprises a plurality of composite splicing blocks, the composite splicing blocks comprise the following raw materials by weight: 40 parts of glass fiber, 50 parts of modified epoxy resin; the modified epoxy resin comprises the following raw materials by weight: 100 parts of epoxy resin, 16 parts of carboxylated nitrile rubber, 5 parts of bisphenol A glycidyl ether, 8 parts of polyetheramine, 0.4 parts of antioxidant, 6 parts of preservative, 80 parts of curing agent, 0.5 parts of accelerator, 5 parts of nano filler; the nano filler is nano silicon dioxide with a particle size of 20-50nm. The curing agent is methyl tetrahydrophthalic anhydride. The accelerator is 2-ethyl-4-methylimidazole. The antioxidant is a hindered phenol antioxidant. The preservative is a flaky zinc-aluminum composite.

[0039] The preparation method of the modified epoxy resin is as follows: Step 1, mixing the nanofiller and the silane coupling agent in a mass ratio of 100:1.3, then adding them to anhydrous ethanol, ultrasonically dispersing them at a frequency of 55 kHz for 30 minutes, the weight volume ratio of the nanofiller to the anhydrous ethanol being 1:3.2, and then vacuum drying them at 60° C. for 2.2 hours to remove the solvent, thereby obtaining a surface-modified nanofiller; Step 2, adding carboxylated nitrile rubber, bisphenol A glycidyl ether, polyetheramine and the surface-modified nanofiller of step 1 to the epoxy resin, stirring at a speed of 500 rpm for 90 minutes to make it uniformly dispersed; Step 3, adding antioxidants and preservatives to the mixture obtained in step 2 in sequence, stirring for 1 hour, and then further dispersing using a three-roll mill at a speed of 200 rpm for 30 minutes to mix well; Step 4, adding the curing agent and the accelerator to the mixed material obtained in step 3, stirring at a speed of 320 rpm for 35 minutes, mixing, and then degassing at a vacuum degree of -0.1 MPa for 25 minutes until there are no bubbles on the surface; Step 5, pre-curing the material after the degassing treatment in step 4 at a temperature of 115° C. for 2 hours.

[0040] The preparation method of the flaky zinc-aluminum composite is as follows: Step A, dissolving zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) in deionized water, the weight volume ratio of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) to water is 112 g:1 L, and the molar ratio of zinc to aluminum is 2:1; Step B, prepare 0.5 mol / L NaOH and 0.1 mol / L Na2CO3 solution, mix them in a volume ratio of 1:1, and add them dropwise to the solution obtained in step A until the pH value is 9-10. After the addition is completed, continue to stir and react for 2.5 hours until a milky white precipitate is generated; Step C, adding the material mixture after the reaction in step B into a high-pressure reactor, hydrothermally aging for 24 hours at a stirring speed of 180 rpm and 75° C., then centrifuging at 9500 rpm for 10 minutes, collecting the precipitate, repeating the centrifugation 3 times, and then washing the obtained precipitate once with deionized water, and then washing twice with anhydrous ethanol (to reduce particle agglomeration during drying), and finally vacuum drying at a temperature of 60° C., a vacuum degree of ≤-0.09 MPa, and a drying time of 24 hours to obtain a flaky zinc-aluminum composite.

[0041] The method for preparing the above-mentioned combined composite cylindrical shell comprises the following steps: Step S1, pretreatment of glass fiber: soaking the glass fiber in a 5% silane coupling agent aqueous solution for 28 minutes, and then drying at 115° C. for 2.5 hours; Step S2, pouring the pre-cured modified epoxy resin into a dipping tank, maintaining the temperature at 88° C., passing the pre-treated glass fiber through the dipping tank, and controlling the dipping speed at 0.3 m / min to make the glass fiber evenly impregnated with the modified epoxy resin; Step S3, preheating the mold to 140° C., extruding the impregnated glass fiber into the mold through an extruder at a speed of 1 m / min to form a block, and then curing it at a temperature of 135° C. for 2.5 hours to obtain a composite material splicing block; Step S4, splicing a plurality of composite material splicing blocks to form a cylindrical shell structure, and then using a carbon fiber composite material to continuously circumferentially wind three layers on the outside of the cylindrical shell with a winding tension of 100N / bundle, to obtain a composite material cylindrical shell.

[0042] Comparative Example 1 A combined composite cylindrical shell and a preparation method thereof, wherein the raw materials of the composite splicing blocks include glass fiber and epoxy resin, and the rest are the same as in Example 1.

[0043] Comparative Example 2 A composite cylindrical shell and a preparation method thereof, wherein the modified epoxy resin comprises, by weight, 100 parts of epoxy resin, 25 parts of carboxylated nitrile rubber, 0.4 parts of antioxidant, 7 parts of preservative, 75 parts of curing agent, 1 part of accelerator, and 6 parts of nanofiller; the nanofiller is nano silicon dioxide with a particle size of 20-50 nm. The curing agent is methyltetrahydrophthalic anhydride. The accelerator is 2-ethyl-4-methylimidazole. The antioxidant is a hindered phenol antioxidant. The preservative is zinc phosphate. The rest is the same as in Example 1.

[0044] The tensile strength, elongation at break and tensile elastic modulus of the composite material splicing blocks obtained in Examples 1-4 and Comparative Examples 1-2 were tested with reference to GB / T 1447-2005-Test Methods for Tensile Properties of Fiber Reinforced Plastics. The compressive stress of the material was tested according to the method specified in GB / T5258-2008.

[0045] The composite material splicing blocks obtained in Examples 1-4 and Comparative Examples 1-2 were tested for compressive strength perpendicular to the fiber direction according to standard ASTM D6641 using a universal testing machine (instron 34TM-50).

[0046] The test results are shown in Table 1.

[0047] Table 1. Performance test results

[0048] It can be seen from Table 1 that the tensile strength and compressive strength of the composite cylindrical shell splicing block using the technical solution of the present invention are improved.

[0049] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0050] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A composite cylindrical shell, characterized in that: The cylindrical shell includes a plurality of composite material splicing blocks, and the composite material splicing blocks include the following raw materials by weight: 40-60 parts of glass fiber and 30-50 parts of modified epoxy resin; the modified epoxy resin includes the following raw materials by weight: 100 parts of epoxy resin, 15-20 parts of carboxyl nitrile rubber, 5-10 parts of bisphenol A glycidyl ether, 5-10 parts of polyether amine, 0.3-0.5 parts of antioxidant, 5-8 parts of preservative, 60-80 parts of curing agent, 0.5-1.5 parts of accelerator, and 5-8 parts of nano filler; The preparation method of the modified epoxy resin is as follows: Step 1, mixing the nanofiller and the silane coupling agent in a mass ratio of 100:0.8-1.3, then adding them to anhydrous ethanol, performing ultrasonic dispersion at a frequency of 40-60kHz for 20-40 minutes, and then vacuum drying and removing the solvent to obtain a surface-modified nanofiller; Step 2, adding carboxylated nitrile rubber, bisphenol A glycidyl ether, polyetheramine and the surface-modified nanofiller of step 1 into the epoxy resin, and stirring to make them uniformly dispersed; Step 3, adding antioxidants and preservatives to the mixed material obtained in step 2 in sequence, stirring and mixing; Step 4, adding the curing agent and the accelerator to the mixed material obtained in step 3, stirring at a speed of 250-350 rpm for 20-40 minutes, mixing, and then degassing under vacuum conditions for 20-40 minutes until there are no bubbles on the resin surface; Step 5, pre-curing the material after degassing in step 4 at a temperature of 100-120° C. for 1.5-2.5 hours.

2. The combined composite cylindrical shell according to claim 1, characterized in that: The nano filler is nano silicon dioxide with a particle size of 20-50 nm.

3. The combined composite cylindrical shell according to claim 1, characterized in that: The curing agent is methyltetrahydrophthalic anhydride.

4. The combined composite cylindrical shell according to claim 1, characterized in that: The accelerator is 2-ethyl-4-methylimidazole.

5. The combined composite cylindrical shell according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant.

6. The combined composite cylindrical shell according to claim 1, characterized in that: The preservative is a flaky zinc-aluminum complex.

7. The combined composite cylindrical shell according to claim 6, characterized in that: The preparation method of the flaky zinc-aluminum composite is as follows: Step A, dissolving zinc nitrate hexahydrate and aluminum nitrate nonahydrate in deionized water, wherein the molar ratio of zinc to aluminum is 2-3:1; Step B, stirring and reacting for 2-4 hours under alkaline conditions of pH = 9-10 to generate a precursor precipitate; Step C, hydrothermally aging at 60-80° C. for 12-24 hours, followed by washing and drying to obtain a flaky zinc-aluminum composite.

8. The method for preparing a combined composite cylindrical shell according to any one of claims 1 to 7, characterized in that: The method for preparing the composite material splicing block comprises the following steps: Step S1, pretreatment of glass fiber: soaking the glass fiber in a 3%-5% silane coupling agent aqueous solution for 20-30 minutes, and then drying at 100-120° C. for 2-3 hours; Step S2, pouring the pre-cured modified epoxy resin into a dipping tank, maintaining the temperature at 80-90° C., passing the pre-treated glass fiber through the dipping tank, and controlling the dipping speed at 0.3-0.5 m / min, so that the glass fiber is evenly impregnated with the modified epoxy resin; Step S3, preheating the mold to 120-150°C, extruding the impregnated glass fiber into the mold through an extruder at a speed of 0.5-1m / min to form a block, and then curing it at a temperature of 120-150°C for 2-4 hours to obtain a composite material splicing block.

9. The method for preparing a combined composite cylindrical shell according to claim 8, characterized in that: A plurality of composite material splicing blocks are spliced ​​together to form a cylindrical shell structure, and then a carbon fiber composite material is used to continuously circumferentially wind the outside of the cylindrical shell to obtain a composite material cylindrical shell.

Citation Information

Patent Citations

  • Carbon fiber reinforced epoxy resin composite and preparation method thereof

    CN105694372A

  • Modified carbon fiber, preparation method and application thereof and modified carbon fiber epoxy resin composite material

    CN115538170A

  • Continuous pultrusion method for large-diameter composite material solid bar

    CN112123820A

  • High-performance pultrusion epoxy resin composite material for wind power and preparation method thereof

    CN112795143A

  • Epoxy resin-based composite material for wind power pultrusion girder and preparation method of epoxy resin-based composite material

    CN113930054A

Cited By

  • Composite material for electrical fence and preparation method thereof

    CN120209512A

  • A composite material for an electric fence and a method of making the same

    CN120209512B